Bidayuh community's social capital development towards sustainable indigenous tourism in Sarawak, Malaysia - Johari, Shazali (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The aim of this study is to holistically understand the role of social capital and resources in influencing the sustainable indigenous tourism practice of the Bidayuh indigenous community in Malaysia. Lack of specific study on Bidayuh community and tourism participation has created a significant justification for this study as they are the main stakeholders of the rural setting. This study employs a quantitative approach for data elicitation and analysis. Pearson correlation is used as the statistical analysis to measure the relationship of linking, bridging and bonding of the community towards sustainable tourism practice. Overall, the social capital variables had average and strong relationship with the sustainable indigenous tourism dimensions. The community believe that tourism is a dominant tool to develop social capital. However, they are still dependent on the support of outsiders to develop the social capital.